Implementing Hospital Self-Management Policy in Chile: Health Professionals’ Perceptions - Méndez, Claudio A.; Universidad Austral de Chile (2014)
Hospitals have been considered a main component for health systemssuccess. Objective: To describe perceptions from hospital staff regarding the implementationof the hospital self-management policy in two highly complex facilities in Chile. Justification:A successful policy implementation demands aligned health professionals regarding policychanges. Methods: Descriptive and exploratory qualitative study based on semi-structuredinterviews for health professionals from two hospitals in southern Chile. A convenience sampleof nineteen health professionals was selected for interviewing. The interviews’ analysis wasthought as the content analysis technique in its conventional approach. Results: For healthprofessionals, a hospital’s self-management policy is conceptualized from financial autonomy.Human resources for health and organizational capabilities still remain as weaknesses of theimplementation process. Conclusions: Overcoming gaps between design and implementationprocesses are crucial for success in hospital reform implementation.